CELL-TISSUE TECHNOLOGIES AS A COMPONENT OF COMPLEX TREATMENT OF COMPLICATIONS OF DIABETIC FOOT SYNDROME - Крицак, Мирослав (SWorldJournal, 2021)
Wound healing in patients with diabetic foot syndrome has its peculiarities, and therefore requires the use of specific wound care dressings.The analysis of the results of treating 29 patients with complicated forms of diabetic foot with conventional met